2005
DOI: 10.1603/0013-8746(2005)098[0694:pbhmaw]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Plant Bugs (Heteroptera: Miridae) Associated with Roadside Habitats in Argentina and Paraguay: Host Plant, Temporal, and Geographic Range Effects

Abstract: Between November 1999 and September 2001, mirid nymphs (Hemiptera: Miridae) were collected on wild and cultivated plants in central and northern Argentina and southeastern Paraguay. In the laboratory, nymphs were reared until adult emergence. Four (Bryocorinae, Deraeocorinae, Mirinae, and Orthotylinae) of the eight mirid subfamilies were collected during the study. Twenty-two mirid species on 43 putative host plant species were collected in Argentina, and Þve species of mirids on eight plant species were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
6
1
1
Order By: Relevance
“…Most of the species were found to be associated with Asteraceae flower buds. Both MELO et al (2004) and LOGARZO et al (2005) reported much higher abundance, but fewer species than we observed at PET. PAULA & FERREIRA (1998) recorded 1,082 individuals from 96 species of Miridae by using a light trap over 64 months.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Most of the species were found to be associated with Asteraceae flower buds. Both MELO et al (2004) and LOGARZO et al (2005) reported much higher abundance, but fewer species than we observed at PET. PAULA & FERREIRA (1998) recorded 1,082 individuals from 96 species of Miridae by using a light trap over 64 months.…”
Section: Discussioncontrasting
confidence: 46%
“…The most abundant species in their study was Campyloneuropsis cincticornis (Stål, 1860) (Bryocorinae), followed by the mirines Taedia stigmosa (Berg, 1878), Derophthalma fluminensis Carvalho, 1944 and Taylorilygus apicalis (Fieber, 1861). The latter, an exotic species, was the most abundant mirid in the study of LOGARZO et al (2005), representing 87% of the specimens collected. These authors studied mirid-host plant associations for 22 species along road side habitats in Argentina and Paraguay by collecting and rearing more than 35,000 nymphs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both juvenile (larvae) and adult A large number of the true bugs T. apicalis and N. simulans were also identified, mainly in São Vicente do Sul. Despite being native to Africa, T. apicalis is a common species in South America (Logarzo et al 2005). It is polyphagous and may attack bean, lettuce, cotton, sunflower and other crops.…”
Section: Resultsmentioning
confidence: 99%
“…Among the Heteroptera, one species of Miridae represented 22% of individuals captured in the WF treatment (Figure 1). Mirids are omnivorous arthropods along a continuum between zoophagy and fitophagy; they are commonly found on Asteraceae (Logarzo et al 2005), the family to which sow-thistle and marigold belong. Coccinellidae was the most abundant predator taxon.…”
Section: Downloaded By [University Of Guelph] At 20:56 06 October 2012mentioning
confidence: 99%